Interaksi Sosial Para Stakeholder Dalam Meningkatkan Kinerja Pegawai: Studi Kasus pada Karyawan Outsourcing di Universitas Islam Negeri Sunan Kalijaga, Yogyakarta - Chrisma Hari Saputra; Bresca Merina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine how social interactions between stakeholders at Sunan Kalijaga State Islamic University (UIN) Yogyakarta affect the performance of outsourced security guards. In the context of higher education, outsourced security guards hold a strategic position in maintaining campus security, so the dynamics of social relationships involving them, both with internal and external parties, are important aspects to examine. The research approach used was qualitative, combining field observation methods, in-depth interviews with seven key informants, and documentation review. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions using the Miles and Huberman model. The results show that open communication, regular appreciation, and structured coordination contribute significantly to improving motivation, discipline, and the quality of security services. Healthy competition between members encourages increased professionalism, while conflicts that arise in daily interactions can be managed effectively through a persuasive approach and collective support from colleagues and superiors. These findings confirm that the performance of outsourced officers is not solely determined by formal work systems or hierarchical instructions, but also by the quality of social relationships established in the work environment. Thus, positive social interactions play a crucial role in creating optimal performance and can serve as a model for relevant managerial practices for other higher education institutions.